State capitalism and the role of the armed forces in Egypt: In the historical context, the current government and 2016-2023 IMF reforms - Kareem I. Abdallah; Martina Jiránková (World Economy and Policy (WEP), 2024)
This article examines a specific form of state capitalism in Egypt under President Abdel Fattah el-Sisi, characterized by the central role of the military in economic affairs. Following the events of the 2011 Egyptian Revolution, the Egyptian military not only secured its position as a key political player, but also became an integral part of the nation's economic strategy. This role extends to various sectors, which has an impact on the dynamics of markets and private sector participation in them. This paper analyses the developments and implications of this specific military-led economic model, particularly in the historical context and the reforms advocated by the International Monetary Fund. It assesses and addresses the challenges of harmonizing military sector economic activities with IMF recommendations on transparency, fiscal consolidation, and structural reforms. The findings highlight the complex interplay between political power, economic control, and international economic governance, which characterizes the unique challenges Egypt faces in balancing military engagement with market-oriented reforms targeting economic growth.
Keywords: E61; H56; O53; P16; P26; 330; State Capitalism; Military Economy; Egyptian Economic Policy; IMF Reforms; Political Economy